ADVANCED RESEARCH METHOD IN CLIMATE CHANGE AND ENVIRONMENTAL SUSTAINABILITY - Engr Theo Aku Ugah; Prof. Okeke Gerald Ndubuisi; Engr. Prof Sony Emeka Ali; Associate Professor Cynthia Amaka Obiorah Ph.D; Dr. Omatseyione Nesiama; Engr. Cletus Onyemhese Agbakhamen; Engr. Ogheneteme Pupu Okoro (IPHO-Journal of Advance Research in Science And Engineering, 2025)
This paper explores advanced research methodologies employed in the study of climate changeand environmental sustainability. It examines qualitative, quantitative, and “mixed-methods” approaches, emphasizing their applications in climate science. Qualitative methods such as case studies, interviews, and content analysis provide insights into human perceptions, policy frameworks, and socio-economic impacts of climate change (Creswell &Poth, 2018). Quantitative techniques, include statistical modeling, remote sensing, and climate simulations, which enable empirical assessments of environmental changes and future projections (IPCC, 2021). The integration of mixed-methods research, such as participatory action research and integrated assessment models, bridges the gap between scientific data and real-world applications (Cameron, 2014). The idea behind this term paper is to exposit these traditional methods mentioned and other emerging technologies, like big data analytics, machine learning, citizen science, and blockchain, which could be applied in revolutionizing climate research by enhancing predictive capabilities, transparency, and stakeholder participation (Rolnick et al., 2019; van der Aalst, 2018). The paper also addresses ethical considerations, including data privacy, equity, and the inclusion of marginalized communities in sustainability studies (Hulme, 2009). Furthermore, interdisciplinary integration is emphasized as a key challenge in developing holistic climate change solutions (O’Brien et al., 2013). By synthesizing traditional and cutting-edge research methodologies, this study provides a comprehensive framework for advancing climate science and promoting effective environmental sustainability strategies.